Kepuasan Sekolah/Madrasah Terhadap Pelayanan Penerimaan Mahasiswa Baru Tingkat Nasional Pada Perguruan Tinggi Keagamaan - Syukur , Abdul; Asdiqoh, Siti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
In an era of increasingly intense competition among universities, the admission service for new students has become one of the strategic aspects that determine the image and appeal of an institution, including the State Islamic University (UIN) of Salatiga.. The purpose of this study is to determine the satisfaction of the School/Madrasah with the Student Admission Service, and to find out the obstacles and solutions in the new national student admission service at Salatiga State Islamic University. This research uses two types of research, namely quantitative and qualitative. Primary data in this study were obtained from interviews. In this study, the population is all schools in the country and abroad with samples of several schools in Java, Sumatra, Kalimantan, East Nusa Tenggara, Papua and Kinabalu Malaysia. The data collection technique uses a questionnaire to find data from the selected sample, as well as interviews. Research instruments in the form of a list of questions in a questionnaire in the form of google form and interview guidelines and observation guidelines. Satisfaction of the school/madrasah in terms of five aspects shows the results of satisfaction with tangible, reliability, responsibility, assurance and empathy are 89.89%, 86.16%, 86.66%, 89.50%, 89.01% respectively. where the most dominant satisfaction is tangible. The SWOT analysis results state that UIN Salatiga has strengths in terms of services including clean and attractive service rooms, technology-based academic services, face-to-face and online-based academic services, responsive and friendly employees and good operating hours. In terms of opportunities that need to be improved by UIN Salatiga are establishing good communication, mouth by mouth promotion, and school cooperation. In the weakness analysis, there are limited IT human resources. And in the threat analysis that needs to be solved is the lack of knowledge about Islamic education, and the higher cost of education. This study contributes to the development of customer satisfaction theory in the context of public service-oriented higher education.